2021
DOI: 10.3390/ijms22157829
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MORT (ZNF667-AS1) in Cancer—Is There a Possible Role in Gynecological Malignancies?

Abstract: Gynecological cancers (GCs) are currently among the major threats to female health. Moreover, there are different histologic subtypes of these cancers, which are defined as ‘rare’ due to an annual incidence of <6 per 100,000 women. The majority of these tend to be associated with a poor prognosis. Long non-coding RNAs (lncRNAs) play a critical role in the normal development of organisms as well as in tumorigenesis. LncRNAs can be classified into tumor suppressor genes or oncogenes, depending on their functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…Among them, ZNF667-AS1, OIP5-AS1, AL118506.1, AF117829.1, POC1B-AS1, CCDC18-AS1, THUMPD3-AS1 and FLNB-AS1 were risk-related lncRNAs, while SNHG11, HCG18, AL021707.2, UGDH-AS1, LINC00641, FGD5-AS1 and AC245452.1 were protective lncRNAs. ZNF667-AS1 (lncRNA mortal obligate RNA transcript) plays an important role in gynecological cancers and might be a potential diagnostic marker ( Di Fiore et al, 2021 ). OIP5-AS1 (OIP5 antisense transcript 1), highly expressed in the nervous system and involved in the regulation of the cell cycle, is closely associated with neoplastic transformation ( Ghafouri-Fard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ZNF667-AS1, OIP5-AS1, AL118506.1, AF117829.1, POC1B-AS1, CCDC18-AS1, THUMPD3-AS1 and FLNB-AS1 were risk-related lncRNAs, while SNHG11, HCG18, AL021707.2, UGDH-AS1, LINC00641, FGD5-AS1 and AC245452.1 were protective lncRNAs. ZNF667-AS1 (lncRNA mortal obligate RNA transcript) plays an important role in gynecological cancers and might be a potential diagnostic marker ( Di Fiore et al, 2021 ). OIP5-AS1 (OIP5 antisense transcript 1), highly expressed in the nervous system and involved in the regulation of the cell cycle, is closely associated with neoplastic transformation ( Ghafouri-Fard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs were proven to play an integral role in the pathogenesis of allergic disease by regulating the differentiation and apoptosis of hematopoietic stem cells, bone marrow cells, and the activation of monocytes, macrophages, and dendritic cells in immune regulation ( Cheng et al, 2022 ). ZNF667-AS1 has been the focus of recent research on inflammatory conditions and cancer with an emphasis on its function in the control of inflammatory pathways ( Di Fiore et al, 2021 ; Zheng et al, 2021 ; Fan et al, 2022 ; Luan et al, 2022 ; Ma et al, 2022 ; Bohosova et al, 2023 ). Excitingly, we discovered that Liu et al's bioinformatics study ( Liu et al, 2019 ), based on data GSE67472, identified ZNF667-AS1 as an important gene involved in the pathogenesis of asthma, which is also downregulated in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of conditions such as acute and chronic renal insufficiency, HE4 can also indicate gynecological diseases and abnormal changes (72). As a result, a new reliable marker is required for the early detection of OC (73).…”
Section: Exosome Lncrna and Ovarian Cancermentioning
confidence: 99%